RELATIONSHIP BETWEEN INSULIN RESISTANCE AND SERUM CONCENTRATIONS OF RESISTIN AND INSULIN-LIKE GROWTH FACTOR-I(IGF-I) ASSOCIATED WITH INDUCED POLYCYSTIC OVARY SYNDROME IN FEMALE RATS - Muhsin S. G. Al-Moziel Jassim M. A. Alkalby Alaa A. Sawad (Basrah Journal of Veterinary Research)
The present study was carried out to determine the relationship between resistin , Insulin-Like Growth- I (IGF-I) and insulin resistance (IR) in female rats with induced polycystic ovary syndrome( PCOS) model and assess their association. Twenty virgin rats were divided into two equal groups: Control group: included 10 rats were given only single intramuscular injection (i.m) of 0.2 ml pure corn oil for each rat. The second PCOS group: included 10 rats given single i.m of 4 mg estradiol valerate dissolved into 0.2 ml pure corn oil for each rat. After 63 days all rats were sacrificed and blood samples were collected from inferior vena cava to obtain the serum for resistin, insulin, IGF-I, SHBG, FSH, LH and FT concentrations. The results revealed a significant increase in serum resistin, IGF-I, insulin, LH and FT concentrations in PCOS group in comparison with control group (P≤0.05),also a significant(P≤0.05) decrease in sex hormone binding globulin (SHBG) concentration in PCOS group compared with control, while, no significant difference was found in FSH concentration. The presence of insulin resistance may play an important role in the pathogenesis of increase of resistin and IGF-I in rats with induce PCOS